A social realist analysis of learner agency and access to education : the case of Grade 11 learners in public secondary schools in the Makana District, Eastern Cape - Namakula, Halima (Rhodes University, Faculty of Education, Department of Education, 2013)
The South African government has shown enormous commitment to the achievement of "Education for All" (EFA) through its policies premised on the right to basic education for all which is enshrined in the constitution. Central to the South African constitution, is a fundamental right of all citizens to basic education, equity, redress, and the improvement of quality of schooling. Further, pro-poor funding policies such as school fee exemptions, social grants and, most recently, the designation of 60% of all schools as 'no fee' schools, have made it possible for even the poorest learners to attend school. This has affirmed South Africa's commitment to the achievement of the Millennium Development Goals (MDGs) by 2015. In light of Notwithstanding the progress made in South Africa in universalising education, there are concerns regarding learner access to quality education, especially in poor provinces such as the Eastern Cape where this study is situated. Thus, the purpose of this study is to further understanding of the interface between learners' agency and access to education in two township public high schools in Makana District in the Eastern Cape Province. In doing so, the research addresses the current under-representation in the literature of the voices of learners about their experiences of access to education. Drawing on Margaret Archer's social realist approach to the relationship between structure and agency, the study explores learner agency with the aim of understanding how learners exercise their agency as they struggle to negotiate and overcome difficult and challenging circumstances in order to access education. The data collection was carried out during the academic year 2011, using a qualitative case study approach. Multiple methods of data collection were used. First, data was collected through questionnaires administered to learners. This questionnaire asked for basic information about the schools (for example, subjects, resources and teachers ), parents ( their education, employment, qualification etc.) and learners' aspirations (their role model; where they see themselves in 5 years; which university they would like to attend; and what they would like to become in future). Secondly, observation method was used to collect data that would inform an assessment of the school's structure and cultural practices and the impact these have on learners' access to education. The focus here was also on classroom interaction between learners and teachers, as well as classroom participation, participation in extra-mural activities and voluntary activities, and interaction with peers and others in a variety of school settings. Thirdly, interviews with learners, educators, principals, and parents were used to provide insight about how participants construct their social worlds. In this study the primary data was collected through semi-structured individual and focus group interview. And finally, document analysis was used to analyse the attendance and performance of learners on attendance registers. Findings from this research have enabled new themes and areas for reflection about learner agency to emerge. These themes reflect current and ongoing constraints and enablements towards learners' educational experiences. In particular, themes such as the following have surfaced: learners changing their lives; the desire to succeed; shaping the future; the value of education; family pride; aspirations and careers. This study addressed these developments by examining agency as temporally located reflexive deliberations of learners upon their future goals and present social environment. This allowed for the identification of individuals' future goals in relation to access to education and the strategies that they intend to pursue to achieve them, in relation to their personal and social contexts. The findings show the choices and decisions learners are prepared to make and the strategies they use as they engage with socio-cultural environments. Archer's nuanced approach to agency and structure offers tools to help make sense of learners' equally nuanced way of engaging with various social structures and making considered decisions about their social environment. Key findings of this research suggest that despite the constraining social structures in their homes, communities and schools, learners make decisions and choices that enable them to navigate social contexts to their advantage. Put differently, for learners, social structures provided the impetus for the projects they created, and to this extent enabled rather than constrained their courses of action.
Keywords: Active learning -- Research -- South Africa -- Eastern Cape; Educational equalization -- Research -- South Africa -- Eastern Cape; Student-centered learning -- Research -- South Africa -- Eastern Cape; Competency-based education -- South Africa -- Eastern Cape; Education, Secondary -- Research -- South Africa -- Eastern Cape